Pretransplant Sensitization Against Angiotensin II Type 1 Receptor Is a Risk Factor for Acute Rejection and Graft Loss. Issue 10 (6th August 2013) - Giral, M.; Foucher, Y.; Dufay, A.; Van Huyen, J. P. D.; Renaudin, K.; Moreau, A.; Philippe, A.; Hegner, B.; Dechend, R.; Heidecke, H.; Brouard, S.; Cesbron, A.; et al.
Abstract The angiotensin II type 1 receptor (AT1R) is an emerging target of functional non‐HLA antibodies (Ab). We examined the potential of determining the degree of presensitization against AT1R as a risk factor for graft survival and acute rejection (AR). The study included 599 kidney recipients between 1998 and 2007. Serum samples were analyzed in a blinded fashion for anti‐AT1R antibodies (AT1R‐Abs) using a quantitative solid‐phase assay. A threshold of AT1R‐Ab levels was statistically determined at 10 U based on the time to graft failure. An extended Cox model determined risk factors for occurrence of graft failure and a first AR episode. AT1R‐Abs >10 U were detected in 283 patients (47.2%) before transplantation. Patients who had a level of AT1R‐Abs >10 U had a 2.6‐fold higher risk of graft failure from 3 years posttransplantation onwards (p = 0.0005) and a 1.9‐fold higher risk of experiencing an AR episode within the first 4 months of transplantation (p = 0.0393). Antibody‐mediated rejection (AMR) accounted for 1/3 of AR, whereby 71.4% of them were associated with >10 U of pretransplant AT1R‐Abs. Pretransplant anti‐AT1R‐Abs are an independent risk factor for long‐term graft loss in association with a higher risk of early AR episodes.